(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: The research aims to predict an increase or decrease in temperatures in the future for the period (2010-2099), based on the maximum temperature data of the Benina weather station for the base period (1961-1990) by using the Statistical Downscaling Model (SDSM) technique, which was used as HadCM3 data inputs and Climate Change Scenarios (A2a) (B2a); scenarios adopted by the IPCC in a report known as SRES in 2000 to make projections of climate and the environment based on greenhouse gases. The results of the study proved that the annual average temperature in the Benina meteorological station will take an upward trend during the future periods compared to the base period (1961-1990). This is consistent with all IPCC scenarios, especially during the third period (2070-2099AD) with an increase of 1.8 m◦ from the base period. ◦m. In the spring, the rate of increase will reach 8°C, and it is expected that the summer will witness a decrease in the maximum temperature by 1°C, as well as the case in the autumn, at a rate of 2.7°C, compared to the base period, which threatens the inability of the countries of the world to control and reduce greenhouse gas emissions.